1987
DOI: 10.1152/ajpheart.1987.253.6.h1391
|View full text |Cite
|
Sign up to set email alerts
|

Role of contraction in the structure and growth of neonatal rat cardiocytes

Abstract: The aim of this study was to determine the role of contraction in the regulation of neonatal rat cardiocyte growth in size. To accomplish this objective, experiments were done on four groups of cardiocytes: 1) quiescent cardiocytes attached to a substrate, 2) contracting cardiocytes attached to a substrate, 3) quiescent cardiocytes not attached to a substrate, adn 4) contracting cardiocytes not attached to a substrate. The cardiocytes were grown in both serum-free and serum-supplemented media for up to 1 wk, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Early studies showed that attachment of neonatal or adult cardiac myocytes to a collagen coated, rigid substrate stimulated cellular growth in culture even in the absence of 5. The ECM-integrin-cytoskeletal complex additional mechanical load [38,39]. In retrospect, these participates in cell signaling in vivo findings were consistent with growth-promoting signals arising from focal adhesions as the isolated, quiescent cells Remarkably little is known about the role of costameres attached and spread in culture, but the activation of cell in regulating growth and function of cardiomyocytes in signaling was not explored.…”
Section: Introductionmentioning
confidence: 80%
“…Early studies showed that attachment of neonatal or adult cardiac myocytes to a collagen coated, rigid substrate stimulated cellular growth in culture even in the absence of 5. The ECM-integrin-cytoskeletal complex additional mechanical load [38,39]. In retrospect, these participates in cell signaling in vivo findings were consistent with growth-promoting signals arising from focal adhesions as the isolated, quiescent cells Remarkably little is known about the role of costameres attached and spread in culture, but the activation of cell in regulating growth and function of cardiomyocytes in signaling was not explored.…”
Section: Introductionmentioning
confidence: 80%
“…Growth of neonatal cardiac myocytes in culture is facilitated by contraction and attachment to a substrate. 3435 Marino and colleagues 34 reported that neonatal myocytes cultured in serum-free medium failed to grow when either attachment or contraction was prevented. McDermott and Morgan 35 demonstrated that contractile activity of cultured neonatal myocytes increased the capacity for protein synthesis via an increase in RNA synthesis, supporting a role for contractile activity in myocyte growth.…”
mentioning
confidence: 99%
“…12 In contrast, recent studies have demonstrated that regular rates of contraction in low KC1 medium stimulate growth of adherent neonatal myocytes in culture. 13 In general, the specific mechanisms by which protein synthesis is regulated at either the transcriptional or translational level have not been defined for any growth stimulus.…”
mentioning
confidence: 99%